Total antioxidant capacity in plasma of HIV-infected patients - Chanarat N. (2014)
Total antioxidant capacity (TAC) of fasting EDTA plasma of 33 healthy and 64 HIV-infected patients was determined using H(2)O(2)-peroxidase-ABTS technique. The results revealed that the average TAC in HIV-infected patients was significantly lower than those in healthy normal persons. (0.161 +/- 0.097 vs 0.269 +/- 0.081 mmol/L Trolox equivalent, p < 0.05). Total lymphocytes were also counted using Hycel automatic cell counter and absolute CD4 numbers using Coulter CD4 manual kit. It was interesting that CD4 count was not correlated with the clinical symptoms of the patients. This paper suggests that prediction of severity and monitoring of the disease should be performed by determining both total lymphocyte count and total antioxidant capacity.